Accounting Digitalization Innovation for MSME Success: Financial Statement Preparation Training - Hidayat, Vinny Stephanie; Agustina, Lidya; Tjun, Lauw Tjun; Lingga, Ita Salsalina; Carolina, Yenni; SeTin, SeTin; Marpaung, Elyzabet Indrawati; Susilawati, Christine Dwi Karya (Universitas Mathla'ul Anwar Banten, 2024)
The reason for this community activity is that some MSMEs have yet to report their firm using proper financial statements. On May 20, 2024, at the Cireundeu Traditional Village, a community service event that includes training on creating financial statements for MSMEs takes place. The goal of this training is to improve participants comprehension of the Basic Equation of Accounting and Financial Statements as well as the Digitization of Financial Statements, an innovation that MSMEs will need to embrace in order to grow their businesses and thrive in the increasingly competitive business environment of the digital age. The method used in this community service includes discussion and counseling strategies in addition to case studies (exercises in preparing direct financial statements). Excel templates for digital financial statements as well as comprehensive and methodical information on the fundamental accounting and financial statement equations were provided to the participants. Following the speaker's presentation and Q&A period, the participants had the opportunity to practice creating financial statements in real time with the help of facilitators. After completing this training, participants should be able to create digital financial reports for MSMEs based on their own business needs. After carrying out this community service, it can be concluded that participants have gained an adequate understanding of the basic equations of accounting and the preparation of financial statements, and will use the knowledge from this training for the preparation of MSME financial reports that they carry out.